1984
DOI: 10.1136/bmj.289.6449.874
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac arrhythmias during rewarming of patients with accidental hypothermia.

Abstract: urate, and urea) was examined in 7364 middle aged British men. After allowing for the influence of alcohol consumption on serum biochemistry there was no substantial association of increased blood lead concentration with renal function. There was a weak positive trend towards increased serum urate concentration at high blood lead concentration and a reverse trend for serum urea concentration. These findings differ from those of a previous study carried Cardiac arrhythmias during rewarming of patients with ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
32

Year Published

1992
1992
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 19 publications
0
26
0
32
Order By: Relevance
“…Other investigators have not found this persistence of abnormalities after rewarming. [34][35][36][37][38] Hypothermia leads to altered electrical conduction, causing changes in cardiac rhythm as well. Several large studies of patients with hypothermia induced for surgery for cardiac anomalies appeared in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have not found this persistence of abnormalities after rewarming. [34][35][36][37][38] Hypothermia leads to altered electrical conduction, causing changes in cardiac rhythm as well. Several large studies of patients with hypothermia induced for surgery for cardiac anomalies appeared in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Key words: limb-saving, survival, prognostic factors, osteo sarcoma élést tekintve megfeleltethetőek a csonkoló m űtétek eredményeinek (17,18,30). A javuló eredményekkel párhuzam osan egyre több publikáció foglalkozik a prognosztikai faktorok szerepé vel (8,13,14,20,21,27).…”
Section: Kulcsszavak: Osteosarcoma Végtagmegtartás Prognosztikai Téunclassified
“…Ennek fő célkitűzései: a szív-tüdő m otor (ECC) m űködési idejének csökkentése, eseten ként teljes elhagyása, a m űtéti behatolás lehetőség sze rinti legkisebbre redukálása, a szív és a test lehűtésének m egszüntetése, vagyis norm otherm ián, dobogó szíven végezni a koszorúér-szűkületek, -elzáródások áthidalá sát (4,5,7,13,14,15,16). Természetesen a gyakorlatban ezeket az új, a szívsebész részéről egyre nagyobb felké szültséget igénylő m űtéti technikákat csak lépésről lé pésre lehet kidolgozni úgy, hogy a beteg szám ára ez való ban nagyobb biztonságot, kisebb megterhelést és jobb eredm ényt biztosítson (9,10,18). 1999-ben az ország szívsebészeti centrum aiban összesen 125 k o szorúér-át hidalást végeztek dobogó szíven, szív-tüdő m o to r (ECC) Orvosi Hetilap 2000,141 (40), 2183-2186.…”
Section: Mankin H J Gebhardt M C Jennings L C éS Mtsaiunclassified
See 2 more Smart Citations